2023
DOI: 10.3390/nu15010223
|View full text |Cite
|
Sign up to set email alerts
|

Daucosterol Alleviates Alcohol−Induced Hepatic Injury and Inflammation through P38/NF−κB/NLRP3 Inflammasome Pathway

Abstract: Alcoholic liver disease (ALD) is caused by chronic excessive alcohol consumption, which leads to inflammation, oxidative stress, lipid accumulation, liver fibrosis/cirrhosis, and even liver cancer. However, there are currently no effective drugs for ALD. Herein, we report that a natural phytosterol Daucosterol (DAU) can effectively protect against liver injury caused by alcohol, which plays anti−inflammatory and antioxidative roles in many chronic inflammatory diseases. Our results demonstrate that DAU amelior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…ERK and JNK were unchanged after chronic stress or CGA treatment. p38MAPK is an important member of MAPK, which is not only involved in the cell cycle, development, differentiation, cell death, senescence, and tumorigenesis, but also acts as a specific serine/threonine kinase to regulate inflammation. , A large number of studies have shown that p38 could activate the NF-κB signaling pathway, thereby causing inflammation in some diseases such as IBD, alcohol-induced hepatic injury, lung inflammation, and Parkinson’s. After SB203580 intervention, the phosphorylation level of p65 was significantly reduced, and the transcription and translation levels of TNF were significantly reduced. The intestinal damage was also significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…ERK and JNK were unchanged after chronic stress or CGA treatment. p38MAPK is an important member of MAPK, which is not only involved in the cell cycle, development, differentiation, cell death, senescence, and tumorigenesis, but also acts as a specific serine/threonine kinase to regulate inflammation. , A large number of studies have shown that p38 could activate the NF-κB signaling pathway, thereby causing inflammation in some diseases such as IBD, alcohol-induced hepatic injury, lung inflammation, and Parkinson’s. After SB203580 intervention, the phosphorylation level of p65 was significantly reduced, and the transcription and translation levels of TNF were significantly reduced. The intestinal damage was also significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 36 ] used MG132 to inhibit the NF- κ B pathway and reduce the extent of liver injury. Some natural antioxidants can also protect against IRI through their own antioxidant effects and inhibition of the NF- κ B pathway [ 37 ]. Ischemic preconditioning can also reduce the activation of the NF- κ B pathway during the subsequent IR process to some extent, resulting in a protective effect on organs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that daucosterol intervention can effectively reduce liver injury, reduce liver index, TNF-α and IL-1β/6 expression levels, and attenuate liver injury in mouse models of liver failure by regulating the IL-6/STAT3 signaling pathway [ 94 ]. Daucosterol also plays a key role in the prevention of liver cancer by improving alcohol-induced liver injury through the p38/NF-κB/NLRP3 signaling pathway, as well as preventing liver oxidative stress and lipid accumulation [ 95 ]. Liver fibrosis is an important factor leading to cirrhosis and subsequently liver cancer, and the activation of hepatic stellate cells is the main cause of liver fibrosis.…”
Section: Prevention Of Precancerous Lesionsmentioning
confidence: 99%